ANTIGENICITY STUDY OF T-3262 - IWAI, NOBUHARU; SHIBATA, TETSUO; YONEDA, TOYOAKI (CHEMOTHERAPY, 1988)
We examined the antigenicity and immunological characteristics of T-3262, a new antibacterial drug. The results obtained were as follows: 1. Antibody production against T-3262 was not observed in beagles or rats treated orally with T-3262 for 28 days. 2. Antibody production against T-3262 was not obsearved in rabbits immunized with an emulsion of T-3262 and FREUND'S comdlete adjuvant (FCA). 3. Hapten-specific antibody production against T-3262 was demonstrated by 24-h. Passive cataneous anaphylaxis in rats, employing serum of mice immunized with a mixture of T-3262 coupled to ovalbumin and aluminium hydroxide gel. 4. No anaphylactic syndrome was observed in guinea-pigs actively sensitized with the emulsion of T-3262 and FCA. 5. T-3262 produced no positive COOMBS' test reaction.